COMPARATIVE ANALYSIS OF CENTRAL JAVA AND EAST JAVA PROVINCIAL GOVERNMENT FINANCIAL PERFORMANCE - Mimin Sherlindah; Shofiatul Mila (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This research was intended to analyze financial performance and to determine differences in financial performance of the governments of Central Java and East Java Provinces in terms of local financial independence ratios, PAD effectiveness ratios, expenditure efficiency ratios, revenue growth ratios, SiLPA financing levels, audit opinions, and findings an audit. This research is a quantitative descriptive research with a comparative form (comparison). This research used secondary data in form of Budget Realization Report (LRA) and Inspection Result Report (LHP) of Central Java and East Java Provinces in the 2014-2018 Fiscal Year. Data analysis techniques using financial ratio analysis and analysis of different tests through the Independent Sample t-Test and Mann Whitney test. The results of this research indicate that there are differences in financial performance based on the number of audit findings. However, there is no difference in financial performance based on the ratio of regional financial independence, the effectiveness of PAD, expenditure efficiency, revenue growth, the level of SiLPA financing, and audit opinion on the Central Java and East Java provincial governments.